Green synthesis of reduced graphene oxide and its reinforcing effect on natural rubber composites. (June 2015) - Wu, L.; Qu, P.; Zhou, R.; Wang, B.; Liao, S.
A green and facile approach to produce graphene using an environmentally friendly reagent, namely proanthocyanidin (PC) as a reducing agent was developed. The obtained graphene (PC-rGO) was characterized using Fourier transform infrared spectroscopy, X-ray diffraction, thermogravimetric analysis and X-ray photoelectron spectroscopy, confirming the effective reduction of GO. With the incorporation of PC-rGO into natural rubber (NR) latex, NR/PC-rGO composites were then prepared by an ultrasonically assisted latex mixing and the co-coagulation. The results show that PC-rGO presents a good dispersion and exfoliation in the NR matrix, contributing to an increase in the mechanical performance. Compared with neat NR, the tensile strength, modulus at 300%, and tear strength for NR composites containing 0.9 phr PC-rGO were increased by 50.2%, 154.9% and 65.2%, respectively. With increasing PC-rGO loading, cross-link density and storage modulus of NR composites increase because of the formation of cross-link points and physical interaction between PC-rGO and the matrix.